2018
DOI: 10.1155/2018/4068538
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Self-Care Intervention with the Application of Health Literacy Strategies in Patients with High Blood Pressure and Limited Health Literacy: A Protocol Study

Abstract: The purpose of this study is to assess the effectiveness of a theory-based self-care intervention with the application of health literacy strategies in patients with high blood pressure and limited health literacy. This is a randomized controlled trial, with measurements at baseline and 1 and 3 months follow-up. 100 patients with high blood pressure and limited health literacy will be randomly allocated to either an intervention group or a usual care control group. We will mainly establish the intervention mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In the present study, training self-care behaviors via deploying cognitive therapy principles proved to be fruitful. This is compatible with the results of research by Javadzade et al that addressed the role of psychological factors in self-care among patients with hypertension (25). Meanwhile, cognitive education that focuses on mitigating negative thinking by stopping thought and affirmation may be a convenient intervention in raising the incentive to comply with treatment in HF patients (37).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, training self-care behaviors via deploying cognitive therapy principles proved to be fruitful. This is compatible with the results of research by Javadzade et al that addressed the role of psychological factors in self-care among patients with hypertension (25). Meanwhile, cognitive education that focuses on mitigating negative thinking by stopping thought and affirmation may be a convenient intervention in raising the incentive to comply with treatment in HF patients (37).…”
Section: Discussionsupporting
confidence: 87%
“…Many authors have confirmed the effect of cognitive training on self-care and self-efficacy in hypertensive patients (25), the effect of psychological interventions on self-care in patients with chronic heart failure (26), the effect of cognitive-behavioral therapy on life quality, selfesteem, and psychological situation (27), and the effect of psychosocial intervention on depressed HF patients (28). The results of these studies indicate the point that the efficacy of cognitive-behavioral training is greater than the efficacy of conventional education programs (25)(26)(27)(28). However, some other studies have observed contradictory results in regard to the effect of cognitive therapy (15,29).…”
Section: Introductionmentioning
confidence: 91%
“…The global demographic shift towards ageing, rapid urbanization, and adoption of unhealthy lifestyle behaviors is significantly affecting trends in human health, generally, 1 and in the emergence of non-communicable diseases including hypertension, specifically. 2 Hypertension, a complex and universal health issue, is pervasive within the adult population, bringing an array of associated health issues that may result in a major burden for hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately five billion patients are afflicted with hypertension globally. 1 In the United States of America, with a 24% growth rate and $3.2 trillion of the total spending on healthcare, 40% of hypertensive individuals (50 million people) remain untreated. 3 Likewise, in the Mediterranean region, 26% of the total population is affected by hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that theory-based nursing interventions in CHD management had success in decreasing blood lipid concentrations, blood pressure, and re-hospitalization rate, and may enhance medication adherence, better adaptation to diet modifications and physical activity recommendations, and thus improved QoL (Faroughi et al, 2021;Mohammadpour et al, 2015;Turan Kavradim & Canli Ozer, 2020;Yildiz & Kasikci, 2020). (Akbari et al, 2017;Akhlaghi et al, 2021;Javadzade et al, 2018). However, to the best of our knowledge, no systematic review or meta-analysis has examined the effects of theory-based nursing interventions in CHD management, and no firm conclusion on this issue has been made so far.…”
Section: Introductionmentioning
confidence: 99%